Antibiotic Use in Childhood and Adolescence and Risk of Inflammatory Bowel Disease: A Case–Control Study in the UK Clinical Practice Research Datalink. Issue 3 (2nd July 2019) - Troelsen, Frederikke Schønfeldt; Jick, Susan
Abstract: Background: Inflammatory bowel disease (IBD) causes serious morbidity and disability, and the incidence is increasing. The disease etiology is not well understood, though inflammatory reactions after antibiotic exposure may be associated with development of IBD. We investigated the association between IBD and prior antibiotic use. Methods: We conducted this case–control study among individuals in the United Kingdom Clinical Practice Research Datalink GOLD (CPRD GOLD). Each case of IBD was matched to 4 controls on age, sex, general practice, and registration year in the CPRD GOLD. Antibiotic exposure was classified by ever or never use, number of prescriptions, and class of antibiotic before the index date. Odds ratios were calculated using conditional logistic regression. Results: We identified 461 cases of ulcerative colitis (UC) and 683 cases of Crohn's disease (CD). There was no association between ever use of any antibiotic and UC (odds ratio [OR], 1.02; 95% confidence interval [CI], 0.72–1.44) or CD (OR, 1.01; 95% CI, 0.73–1.39) compared with never use. A slightly increased CD risk was observed among ever users of quinolones (OR, 1.76; 95% CI, 1.00–3.11) and metronidazole (OR, 1.43; 95% CI, 0.87–2.34) compared with never users. CD was associated with antibiotic exposure before age 5 (OR, 2.20; 95% CI, 0.75–6.43) in an analysis restricted to individuals followed from birth. Conclusions: There was no association between UC or CD and overall prior use of antibiotics, though prior use of metronidazole and quinolones was associated with a slightly increased risk of CD. Antibiotic use in early childhood may increase the risk of CD. Abstract : Antibiotic exposure may be associated with development of inflammatory bowel disease; however, studies with long-term prescription records are needed. We therefore conducted a case-control study to investigate the association between prior antibiotic use and subsequent development of IBD in a long-term setting.